2014
DOI: 10.15253/2175-6783.2014000100015
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of women undergoing treatment for cervical cancer

Abstract: This study aimed to evaluate the quality of life of women with cervical cancer. This is a cross-sectional, descriptive study developed with 43 women undergoing oncological treatment assisted at an Oncology High Complexity Center, in the Southern region of Brazil. The instrument used was the European Organization for Research and Treatment of Cancer -Quality of Life Questionnaire Core-30, and the data were analyzed through descriptive statistics. The average age was 54.6 years old. Married women prevailed (53.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Scores were in the range of 0–100, with higher scores indicating higher levels of financial difficulty. Ten studies were not considered for discussion due to concerns about the validity of the results 19,22,23,26–28,45,48,57,59 . Of the remaining studies, there was a wide range in reported results from the survey measure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores were in the range of 0–100, with higher scores indicating higher levels of financial difficulty. Ten studies were not considered for discussion due to concerns about the validity of the results 19,22,23,26–28,45,48,57,59 . Of the remaining studies, there was a wide range in reported results from the survey measure.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies that utilized the EOTTC tool were excluded from evaluation as there were concerns about how the scores were re ported. 20,23,[26][27][28]45,57,58 Most studies reported mean scores of 60-90 22,30,33,44,48,51,55 (range 0-100), indicating relatively positive social support. However, two cross-sectional studies from Indonesia 17 (n = 164) and Ethiopia 19 (n = 404) as well as a cohort study from China 59 (n = 97) reported mean scores below 45.…”
Section: Social Supportmentioning
confidence: 99%
“…Um ponto importante a ser discutido está relacionado à sugestão de se retirar o tema "Efeitos adversos", com a justificativa de que esse tema não se relaciona à braquiterapia ginecológica. No entanto, estudos anteriores (3,6) confirmam que os efeitos adversos apresentados no manual de orientações são também causados pela braquiterapia ginecológica, não sendo somente restritos à radioterapia externa, conforme sugerido pelo profissional. A sugestão de se acrescentar a informação "ingerir o mínimo de água" para pacientes que fazem uso de medicação anti-hipertensiva também não foi acatada, tendo em vista que tal orientação é oferecida verbalmente durante a consulta de enfermagem, para pacientes que farão tratamento com sedação e necessitam de jejum, conforme protocolo institucional.…”
Section: Discussionunclassified
“…Apesar de seus benefícios significativos, esse tratamento produz efeitos adversos que podem se tornar irreversíveis caso não manejados de forma adequada (4)(5) . As principais reações decorrentes da braquiterapia são ardor, dor, náuseas, vômitos, infecção urinária, fraqueza, constipação, diarreia, sangramento vaginal, cansaço, hipersensibilidade vulvar e estenose vaginal (3,6) .…”
Section: Introdução Métodounclassified
“…In this perspective, before the epidemiological characteristics that suggest the impacts of mammary neoplasia in women, we realized there is a vast inte-rest in monitoring the quality of life of the patients in chemotherapy, seeking to measure the side effects induced by the treatment and developing therapies that stimulate a better adaptation to the disease, cancer treatment and nursing care (9) .…”
Section: Introductionmentioning
confidence: 99%